2020
DOI: 10.1111/desc.13023
|View full text |Cite
|
Sign up to set email alerts
|

Is that a pibu or a pibo? Children with reading and language deficits show difficulties in learning and overnight consolidation of phonologically similar pseudowords

Abstract: Word learning is critical for the development of reading and language comprehension skills. Although previous studies have indicated that word learning is compromised in children with reading disability (RD) or developmental language disorder (DLD), it is less clear how word learning difficulties manifest in children with comorbid RD and DLD. Furthermore, it is unclear whether word learning deficits in RD or DLD include difficulties with offline consolidation of newly learned words. In the current study, we em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 87 publications
0
13
1
Order By: Relevance
“…When exposed to novel words through an incidental learning paradigm, preschool-age children with DLD demonstrated poorer retention than their peers (Rice et al, 1994). In a more recent study, third-and fourth-grade children with DLD demonstrated poorer retention of word learning than their peers when tested the following day (Malins et al, 2020). Children's phonological representations of forms were more stringently tested in this study than is typical for word learning studies.…”
Section: Consolidating Words Between Periods Of Inputmentioning
confidence: 93%
See 1 more Smart Citation
“…When exposed to novel words through an incidental learning paradigm, preschool-age children with DLD demonstrated poorer retention than their peers (Rice et al, 1994). In a more recent study, third-and fourth-grade children with DLD demonstrated poorer retention of word learning than their peers when tested the following day (Malins et al, 2020). Children's phonological representations of forms were more stringently tested in this study than is typical for word learning studies.…”
Section: Consolidating Words Between Periods Of Inputmentioning
confidence: 93%
“…During sleep, representations of the form, meaning, and link can be consolidated successfully in that they are strengthened and maintained (Henderson et al, 2012). Consolidation can be less successful, in that after a period of sleep, children remember less about a word than they did before sleep (Malins et al, 2020). Consolidation can also be unsuccessful when encoded representations are forgotten completely (Storkel, 2015).…”
mentioning
confidence: 99%
“…With some exceptions (e.g., Alt et al, 2017Alt et al, , 2019Kamhi et al, 1990;Malins et al, 2020), the comorbidity between DLD and dyslexia has been largely ignored in word learning studies, which complicates the understanding of word learning difficulties in each disorder. To our knowledge, there are only two prior studies that have examined the word learning abilities of children with DLD + dyslexia as compared to children with dyslexia with average language skills (dyslexia-only) and TD children (Alt et al, 2019;Malins et al, 2020). Alt et al (2019) taught second-grade children with DLD + dyslexia, dyslexia-only, and TD the pseudoword names and semantic features of novel objects in six games (i.e., conditions) that manipulated phonological or visuospatial features such as pseudoword length or visual similarity of the novel object referents.…”
Section: Word Learning Difficulties In Children With Dld and Dyslexiamentioning
confidence: 99%
“…With some exceptions (e.g., Alt et al, 2017Alt et al, , 2019Kamhi et al, 1990;Malins et al, 2020) the comorbidity between DLD and dyslexia has been largely ignored in word learning studies, which complicates the understanding of word learning difficulties in each disorder. To our knowledge, there are only two prior studies that have examined the word learning abilities of children with DLD+dyslexia as compared to children with dyslexia with average language skills (dyslexia-only) and TD children (Alt et al, 2019;Malins et al, 2020).…”
Section: Word Learning Difficulties In Children With Dld and Dyslexiamentioning
confidence: 99%
“…With some exceptions (e.g., Alt et al, 2017Alt et al, , 2019Kamhi et al, 1990;Malins et al, 2020) the comorbidity between DLD and dyslexia has been largely ignored in word learning studies, which complicates the understanding of word learning difficulties in each disorder. To our knowledge, there are only two prior studies that have examined the word learning abilities of children with DLD+dyslexia as compared to children with dyslexia with average language skills (dyslexia-only) and TD children (Alt et al, 2019;Malins et al, 2020). Alt and colleagues (2019) taught second-grade children with DLD+dyslexia, dyslexia-only, and TD the pseudoword names and semantic features of novel objects in six games (i.e., conditions) that manipulated phonological or visuospatial features such as pseudoword length or visual similarity of the novel object referents.…”
Section: Word Learning Difficulties In Children With Dld and Dyslexiamentioning
confidence: 99%